Interactions between glutathione S-transferase genes and household air pollution on asthma and lung function - Dai, Xin; Dharmage, Shyamali C.; Lodge, Caroline J. (Frontiers in Molecular Biosciences, 2022)
Oxidative stress is one of the main pathophysiological mechanisms for chronic respiratory disease. Glutathione S-transferase (GST) genes play important roles in antioxidant defences and may influence respiratory health. Although there is not consistent evidence that the three commonly studied genes of GSTM1, GSTT1 and GSTP1 are associated directly with respiratory outcomes, they seem to be related to disease susceptibility if exposure interactions are taken into account. Exposure to household air pollution may be particularly important in increasing lung oxidative stress. This review summarizes the relationships between GST genes, household air pollution and asthma and impaired lung function. Our findings support a role for GST polymorphisms in susceptibility to asthma and impaired lung function via oxidative stress pathways. Future research should additionally consider the role of gene-gene interactions, multiple environmental exposures, gender and in these complex associations, which are involved in maintaining antioxidant defences and lung health.